2022
DOI: 10.1021/acs.est.2c03673
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Control of Traditional Iron–Carbon Electrodes to Regulate the Oxygen Reduction Route to Scale Up Water Purification

Abstract: Shifting four-electron (4e–) oxygen reduction in fuel cell technology to a two-electron (2e–) pathway with traditional iron–carbon electrodes is a critical step for hydroxyl radical (HO•) generation. Here, we fabricated iron–carbon aerogels with desired dimensions (e.g., 40 cm × 40 cm) as working electrodes containing atomic Fe sites and Fe3C subnanoclusters. Electron-donating Fe3C provides electrons to FeN4 through long-range activation for achieving the ideal electronic configuration, thereby optimizing the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 56 publications
0
12
0
Order By: Relevance
“…Previous work has indicated that the introduction of iron would favor the competitive 4e − oxygen reduction to H 2 O. 31 According to the experimental results of RRDE measurements (Figure 2b), the increased Fe content in the cathode reduced the H 2 O 2 selectivity. Although the presence of Fe can act as Fenton catalyst to decompose the generated H 2 O 2 into HO • , it is very hard to quantify relationship between HO • and the content of Fe.…”
Section: •−mentioning
confidence: 69%
See 4 more Smart Citations
“…Previous work has indicated that the introduction of iron would favor the competitive 4e − oxygen reduction to H 2 O. 31 According to the experimental results of RRDE measurements (Figure 2b), the increased Fe content in the cathode reduced the H 2 O 2 selectivity. Although the presence of Fe can act as Fenton catalyst to decompose the generated H 2 O 2 into HO • , it is very hard to quantify relationship between HO • and the content of Fe.…”
Section: •−mentioning
confidence: 69%
“…The iron−nickel codoped carbon aerogel (denoted FeNiC) was synthesized through sol−gel formation, solvent exchange, and pyrolysis according to a modified method that was already reported in our previous work. 31 First, resorcinol, formaldehyde, sodium carbonate, and deionized water were mixed in a certain mole ratio to form a homogeneous solution. Then quantitative iron and nickel precursors (C 15 H 21 FeO 6 and C 10 H 14 NiO 4 ) were added into the solution, which was then poured into a transparent cuboid glass with a spacing of 5 mm, followed by reaction at 30 °C, 50 °C for 1 day, and 90 °C for 3 days.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
See 3 more Smart Citations